Darkside / 1. - Becker, Tom (Becker, Tom. Darkside, 2008)
Jonathan Starling's father is in an asylum and his home has been attacked when, while running away from kidnappers, he stumbles upon Darkside, a terrifying and hidden part of London ruled by the descendents of Jack the Ripper, where Jonathan is in mortal danger if he cannot find the way out.